Hybrid Finite Element - Wave Based Method for acoustic problems - Hal, Bas van; Desmet, Wim; Vandepitte, Dirk; Sas, Paul (Computer Assisted Methods in Engineering and Science, 2023)
The finite element method (FEM) is widely accepted for the steady-state dynamic response analysis of acoustic systems. It exhibits almost no restrictions with respect to the geometrical features of these systems. However, its application is practically limited to the low-frequency range. An alternative method is the wave based method, which is an indirect Trefftz method. It exhibits better convergence properties than the FEM and therefore allows accurate predictions at higher frequencies. However, the applicability is limited to systems of moderate geometrical complexity. The coupling between both methods is proposed. Only the parts of the problem domain with a complex geometry are modelled using the FEM, while the remaining parts are described with a wave based model. The proposed hybrid method has the potential to cover the mid-frequency range, where it is still difficult for currently existing (deterministic) techniques to provide satisfactory prediction results within a reasonable computational time.